Katharine Susannah Prichard’s Coonardoo and Rachel de Queiroz’s The Year Fifteen: a settler colonial reading - Deborah Scheidt (Ilha do Desterro, 2019)
Settler Colonial Studies is a theoretical approach being developed in Australia by Lorenzo Veracini (2010, 2015, 2016), inspired by Patrick Wolfe’s (1999, 2016) precursor theories. It proposes a differentiation between “colonialism” and “settler colonialism” based on the premise that the latter involves land dispossession and the literal or metaphorical disappearance of Indigenous Others, while the former is mainly concerned with the exploitation of Indigenous labour and resources. The fact that settlers “come to stay” is a crucial element in positing settler colonialism as “a structure”, whereas colonialism would be “an event” in the lives of the colonised Others. This paper adopts settler colonial theories to propose a comparative study of two modernist “social” novels by women writers in Australia and Brazil: Katharine Susannah Prichard’s Coonardoo (1929) and Rachel de Queiroz’s The Year Fifteen (1930). Both novels deal with exploitation, discrimination, racism and the dispossession of the Indigenous Other and their miscegenated descendants, from a non-Indigenous, i.e. “settler”, perspective. Elements that are crucial for settler colonialism, such as ambivalence, indigenisation and mechanisms of disavowal and transfer in several of their guises, are examined, compared and contrasted.